Intelligent Computing & Optimization - Vasant, Pandian; Zelinka, Ivan.; Weber, Gerhard-Wilhelm.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes innovative research work presented at ICO'2018, the 1st International Conference on Intelligent Computing and Optimization, held in Pattaya, Thailand on October 4-5, 2018. The conference presented topics ranging from power quality, reliability, security assurance, cloud computing, smart cities, renewable energy, agro-engineering, smart vehicles, deep learning, block chain, power systems, AI, machine learning, manufacturing systems, and big-data analytics. This volume focuses on subjects related to innovative computing, uncertainty management and optimization approaches to real-world problems in big-data, smart cities, sustainability, meta-heuristics, cyber-security, IoTs, economics and finance, renewable energy, energy and electricity systems, and block chain. Presenting cutting-edge methodologies with real-world application problems and their solutions, the book is useful for researchers, managers, executives, students, academicians, practicing scientists, and decision makers from all around the globe. It offers the academic and the applied communities a compendium and a research resource with significant insights and inspiration for innovative scientific education, investigation and collaboration, to overcome "hard problems" among the emerging challenges today and in the future.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence